2021
DOI: 10.18502/ijph.v50i12.7950
|View full text |Cite
|
Sign up to set email alerts
|

Time-Driven Activity Based Costing of Speech Therapy in a Small-Scale Rehabilitation Clinic

Abstract: The article's abstract is not available.  

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Analyzing the cost structure for selected rehabilitation services in the Nezam-Mafi Rehabilitation Center showed that the share of different costs in these services was different depending on the type of service. Personnel costs allocate the highest share in physiotherapy services, as emphasized in many previous studies [4,17,20,22].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Analyzing the cost structure for selected rehabilitation services in the Nezam-Mafi Rehabilitation Center showed that the share of different costs in these services was different depending on the type of service. Personnel costs allocate the highest share in physiotherapy services, as emphasized in many previous studies [4,17,20,22].…”
Section: Discussionmentioning
confidence: 91%
“…Following the purpose of the study, it was observed that the cost of providing most rehabilitation services in the Nezam-Mafi Rehabilitation Center is higher than the government tariffs for these services. Although Nezam Mafi Rehabilitation Center is a government service provider institution whose losses are compensated by the government budget, other rehabilitation centers likely run similarly [16,17].…”
Section: Discussionmentioning
confidence: 99%